Pengaruh kepercayaan terhadap loyalitas nasabah pada perumda BPR Majalengka Cabang Jatitujuh Kabupaten Majalengka - Pratiwi, Mega Dwi; Mega Ayu Nurhayati (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to determine the effect of trust on customer loyalty. Where the independent variable is trust affects customer loyalty as the dependent variable. This research was conducted at Perumda BPR Majalengka, Jati Tujuh Branch, Majalengka Regency. The data collection method in this study was a questionnaire filled out by respondents, namely the customers of Perumda BPR Majalengka Jati Tujuh Branch, Majalengka Regency. A sampling of 95 respondents in this study using a simple sampling method. The independent variable in this study is trust, while the dependent variable is customer loyalty. The analysis used in this research includes analysis of validity test, reliability test, linear regression analysis, correlation analysis and coefficient of determination, hypothesis testing t-test. The hypothesis test shows that the value of t arithmetic = 13.8048 where the value of t table = 1.66140, So it is evident that there is a significant influence between trust and customer loyalty. Then H0 is rejected, and H1 is accepted because t count > t table or 13.8048 > 1.66140. The regression equation is Y= 3.76 + 0.43X. from the equation, it can be concluded that the constant value of 3.76 states that if there is no increase in the value of the X variable, the price of customer loyalty is 3.76. The regression coefficient of 0.43 states that for each addition (because of the + sign), one score, the value of confidence will increase in a score of 0.43 times. So every 1-time increase in score is predicted to increase customer loyalty by 0.43X. From the above calculation results where the correlation coefficient (r) = 0.7358, which means that the relationship between trust and customer loyalty is quite strong according to the interpretation of the r-value against the interpretation table of the r-value. From the calculation results, the coefficient of determination is 54.14%, which shows trust's contribution (variable X) to the rise and fall of customer loyalty (variable Y) of 54.14%. In comparison, the remaining 45.86% was influenced by other factors not discussed in this study and considered unchanged (ceteris paribus).